2018
DOI: 10.3390/w10091129
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bubble Characteristics on Chute Spillway Bottom

Abstract: Chute aerators introduce a large air discharge through air supply ducts to prevent cavitation erosion on spillways. There is not much information on the microcosmic air bubble characteristics near the chute bottom. This study was focused on examining the bottom air-water flow properties by performing a series of model tests that eliminated the upper aeration and illustrated the potential for bubble variation processes on the chute bottom. In comparison with the strong air detrainment in the impact zone, the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…e CFD-PBM coupled model is of high value for applications in the gas-liquid twophase flow in hydraulic engineering, and the accuracy and reliability were validated through the physical model experiments of Bai et al [7,28]. e experiments were conducted in a 0.25 m wide rectangular chute with a bottom slope of 14°.…”
Section: Computational Model Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…e CFD-PBM coupled model is of high value for applications in the gas-liquid twophase flow in hydraulic engineering, and the accuracy and reliability were validated through the physical model experiments of Bai et al [7,28]. e experiments were conducted in a 0.25 m wide rectangular chute with a bottom slope of 14°.…”
Section: Computational Model Layoutmentioning
confidence: 99%
“…Small bubbles support to alleviate cavitation erosion, even at the same air concentration. Bai et al [7] measured and analyzed the development of bubble characteristics downstream of the spillway aeration facility by using a conductivity probe. It was found that the chord length of bubbles decreased sharply in the impact zone.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal atmospheric pressure, researchers have conducted extensive research on using air entrainment to alleviate cavitation. Research directions mainly encompass the mechanisms of using air entrainment to alleviate cavitation [10,11], the characteristics of forced aeration in water flow [12][13][14][15], the design of aeration devices [16], the downstream bubble characteristics of aeration devices [17], and the scale effects of aeration ratios [18,19]. The ventilation volume is an important parameter for measuring the effectiveness of air entrainment devices.…”
Section: Introductionmentioning
confidence: 99%
“…Juan César Luna-Bahena et al [12] studied the combined effect of the top pier and bottom aeration facilities of a smooth spillway. Bai et al [13][14][15] studied the characteristics of microscopic bubbles near the bottom of a drain tank, revealed the flow characteristics of air and water at the bottom, and proposed a self-similar relationship between air concentration and bubble frequency in various regions. Bai et al [16] proposed a method to estimate the air entrainment rate of a slot bed by considering the effective air cavity length and the influence of air escaping the jet.…”
Section: Introductionmentioning
confidence: 99%